SYNTHESIS AND CHARACTERIZATION OF NiO-TiO2/GRAPHENE AS A CANDIDATE ANODE FOR LITHIUM-ION BATTERY DEVELOPMENT - Muh Edihar; Kaharuddin Kaharuddin; Irwan Irwan; Maulidiyah Maulidiyah; Shohibul Faqih; Mawaddah Zaqinah Diah; Thamrin Azis; Muhammad Nurdin (UPT Publication and Journal Management, Islamic University of Kalimantan, 2025)
This study synthesizes and characterizes NiO–TiO₂/graphene nanocomposites as anode materials to enhance the performance of lithium-ion batteries (LIBs). The composite was prepared using NiO precipitation, TiO2 annealing, and hydrothermal methods. FTIR analysis identified -OH stretching vibrations at 3313.63 cm-1 and Ni-O/Ti-O bonds at 624 cm-1, confirming metal oxide formation. XRD revealed anatase TiO2 phases at 2θ = 25° and 48° with (101) and (200) planes, rutile phases at 2θ = 27°, 36°, and 54° with (110), (101), and (211) planes, and peaks for graphene (2θ = 43°) and NiO (2θ = 62° and 70°). SEM-EDX showed uniform nanoparticle morphology with Ti, O, Ni, and C elements. Cyclic voltammetry indicated a 5% capacity increase per cycle over five cycles, with oxidation at 0.75 V and reduction at -0.75 V. The composite demonstrated excellent electrochemical stability and enhanced storage capacity, highlighting its potential as an anode material for LIBs.